Stereoselective Preparation of (4S)-1-Methyl-4-propyl-L-proline Commencing from (cis)-4-Hydroxy-L-proline - Gour Hari Mandal; Shifali Choudhary; Steven P. Kelley; Shyam Sathyamoorthi (Molbank)
We present a recipe for the stereoselective conversion of commercial (cis)-4-hydroxy-L-proline into (4S)-1-methyl-4-propyl-L-proline, an analog of the amino acid fragment found in the clinically used antibacterial antibiotic lincomycin. The single-crystal X-ray diffraction analysis of the final target’s hydrochloride salt confirms its identity and absolute stereochemistry.